An Enhanced Audio Encryption Method using Unicode and Dynamic Message Mapping in Elliptic Curve Cryptography - M, Sreekala; Varghese Paul; Ratheesh T K; Sonia Sunny (INFOCOMP Journal of Computer Science, 2023)
This paper presents a novel paradigm for audio cryptosystems that uses elliptic curve encryption to secure audio data. It has the goal of increasing the level of security in digital audio transmission. The suggested method works by mapping an audio message into an Elliptic Curve, then encrypting and decrypting it. This work's uniqueness stems from the use of ECC for encryption, which is the first of its type in audio streaming. The choice of an acceptable mapping method was difficult; hence the dynamic mapping method was used. ECC was chosen for encryption because it is a discrete logarithm problem that is not susceptible to attack by quantum computers. Different audio samples representing bird sound, lion sound, and music sound were used to assess the performance of the recommended cryptosystem. The proposed model's usefulness for quick audio encryption and computational simplicity has been demonstrated. Various statistical analyses have been performed on the suggested model, and the results show that audio signals are better protected from various security risks.